DIURON INDUCED PHYTOTOXICITY IN COTTON GROWN ON RED AND BLACK SOILS - MD. MIFTA FAIZULLAH,; T. RAMPRAKASH,; T. ANJAIAH,; M. MADHAVI, (The Bioscan, 2020)
The experiment comprised of seven treatments having varied doses of diuron 80% WP at 0.5 kg ha -1 , 0.75 kg ha 1 , 1.0 kg ha -1 and pendimethalin 38.7% CS (677 g ha -1 ) as preemergence (PE) application followed by postemergence application of pyrithiobac sodium10% EC (62.5 g ha -1 ) + quizalofop ethyl 5% EC (50.0 g ha -1 ). Non-chemical weed management treatments comprised of polyfilm, mechanical weeding (at 20, 40 and 60 days after sowing) and unweeded control. In red soil no phytotoxicity symptoms were observed in any of the herbicide treatments, but slight yellowing of seedlings was observed in diuron 1.0 kg ha -1 PE at 10 and 15 days after herbicide spray (DAHS) but the seedlings recovered completely at 10 DAHS. Phytotoxicity symptoms in black soils were manifested as severe yellowing of emerged cotton seedlings at 10 and 15 DAHS and the yellowing with reduced intensity persisted upto 30 and 45 DAHS in diuron 1.0 kg ha -1 PE treatment In the same treatment, necrosis was observed at 10 DAHS which was more pronounced at 15 DAHS and at 30 DAHS the necrotic symptoms were gradually reduced and disappeared. Seedling mortality was also observed in diuron 1.0 kg ha -1 in black soils which was severe at 15 DAHS, slight mortality at 30 DAHS and after 30 DAHS no mortality was observed.